Valve sparing surgery in an adult patient with dextrocardia and annuloaortic ectasia - Zeybek, Rahmi; Bacaksiz, Ahmet; Sharifov, Rasul; Sevgili, Emrah; Ay, Yasin (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
We report the case of a patient with situs inversus totalis, annuloaortic ectasia complicated by aortic insufficiency and mitral regurgitation which induced congestive heart failure. Both valvular lesions were repaired physiologically using aortic root sparing Yacoub ‘remodeling’ technique and mitral ring annuloplasty. Valve sparing techniques can be used effectively even in patients with complicated clinical scenarios (like dextrocardia and annuloaortic ectasia) to avoid the potential risks related to prosthetic valve implantation and lifelong anticoagulation therapy.